The Measurement of Firm Diversification: Some New Empirical Evidence - Montgomery, Cynthia A. (Academy of Management Journal, 1982)
Two approaches to the measurement of firm diversification are compared: (1) continuous SIC-based product count measures and (2) categorical measures as popularized by Rumelt. The measures are found to be more similar than previous research has suggested, although each appears to have advantages for particular research topics and methodological approaches.